2017
DOI: 10.4103/ijpsym.ijpsym_364_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors associated with Depression among Clinically Stable People Living with HIV/AIDS on Antiretroviral Therapy

Abstract: Background: Individuals with HIV/AIDS are prone for psychiatric/psychological morbidities. Many studies have reported significantly higher prevalence of depression in people living with HIV/AIDS (PLWHA's) when compared to general population. However, there are only very few studies looking at the prevalence of depression in patients on antiretroviral therapy (ART). Objectives: To estimate the prevalance and factors associated with depression among clinically stable PLWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Prevalence of depression among HIV-infected people was found to be 47%-69% in India according to various studies by NACO, Bhat et al and Rai et al 2,4,7 Depression among PLHA in the study was 33.5%, which was similar to the findings of 30% depression among clinically stable PLHA at ART centre of Thissur government medical college. 12 A study done at Aligarh using PHQ 9 questionnaire found 16.1% of PLHA were suffering from depression with 13.1% having mild, 2.3% moderate and 0.7% moderately-severe depression, whereas in this study 19.9% of study participants had mild depression, 10.5% moderate and 3.1% had moderately severe depression. 13 This study revealed that among PHLA, proportion of depression was more among females 40.3% compared to males 24.8%, which was statistically significant (p=0.003) which was similar to studies done by Chandra et al and Dhadphale et al in India.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Prevalence of depression among HIV-infected people was found to be 47%-69% in India according to various studies by NACO, Bhat et al and Rai et al 2,4,7 Depression among PLHA in the study was 33.5%, which was similar to the findings of 30% depression among clinically stable PLHA at ART centre of Thissur government medical college. 12 A study done at Aligarh using PHQ 9 questionnaire found 16.1% of PLHA were suffering from depression with 13.1% having mild, 2.3% moderate and 0.7% moderately-severe depression, whereas in this study 19.9% of study participants had mild depression, 10.5% moderate and 3.1% had moderately severe depression. 13 This study revealed that among PHLA, proportion of depression was more among females 40.3% compared to males 24.8%, which was statistically significant (p=0.003) which was similar to studies done by Chandra et al and Dhadphale et al in India.…”
Section: Discussioncontrasting
confidence: 51%
“…7 No statistical association was found between CD4 count and depression in the present study which was similar to findings of study at Jhansi and few other studies. 7,12,16 Proportion of Depression was 65.5% among PLHA with less than one year of illness compared to 28.6% among PLHA with 5 years of illness, which was statistically significant (p=0.001). Similarly duration of ART was statistically associated with depression, as 61.1% of PLHA on ART for less than 1 year had depression compared to 28.6% of depression among PLHA who were on treatment for more than 5 years, but in other studies duration of illness or duration of ART were not associated with depression.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sir, I read the article by Algoodkar et al with considerable interest. [1] The authors reported the prevalence of depression in 100 people living with HIV/AIDS (PLWHAs) undergoing treatment in an antiretroviral therapy (ART) center to be 30%. These findings imply the need for regular screening of PLWHAs undergoing ART for depressive symptoms and appropriate mental health care according to the results of the screening.…”
Section: A Comment On "Prevalence and Factors Associated With Depression Among Clinically Stable People Living With Hiv/aids On Antiretromentioning
confidence: 99%
“…Currently, Iran has reached the HIV epidemic proportion and it is more prevalent among high-risk groups, such as prisoners, substancedependents, and sex workers (Joulaei, Lankarani, Kazerooni & Marzban, 2017). People Who Live with HIV (PWLH), as a chronic and disabling disease, experience high levels of anxiety (Brandt et al, 2017), depression (Bhatia & Munjal 2014), sleep disorders (Gamaldo et al, 2013), suicidal ideation (Ruffieux et al, 2019), impaired sexual function (Khuat et al, 2018), impairments in daily living activities, and socio-psychological pressures (Russell et al, 2016). There is no definitive cure for HIV; thus, patients accept the feelings of helplessness and inefficiency, instead of managing and controlling the disease.…”
Section: Introductionmentioning
confidence: 99%